2015
DOI: 10.1093/scan/nsv104
|View full text |Cite
|
Sign up to set email alerts
|

Distinct frontal and amygdala correlates of change detection for facial identity and expression

Abstract: Recruitment of ‘top-down’ frontal attentional mechanisms is held to support detection of changes in task-relevant stimuli. Fluctuations in intrinsic frontal activity have been shown to impact task performance more generally. Meanwhile, the amygdala has been implicated in ‘bottom-up’ attentional capture by threat. Here, 22 adult human participants took part in a functional magnetic resonance change detection study aimed at investigating the correlates of successful (vs failed) detection of changes in facial ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In other words, in the early stage of attention, evolutionarily threatening information captured attention faster than temporarily goal-relevant information. Previous research suggested evolutionarily threatening information can lead to the "bottom-up" capture of attention [52][53][54] . This result supported Theeuwes' Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, in the early stage of attention, evolutionarily threatening information captured attention faster than temporarily goal-relevant information. Previous research suggested evolutionarily threatening information can lead to the "bottom-up" capture of attention [52][53][54] . This result supported Theeuwes' Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…While this “intrinsic connectivity” is different from pure resting-state connectivity previous studies have shown that it exhibits a very similar functional connectivity pattern reflecting the inherent connectivity of the large-scale networks in the brain ( Korgaonkar et al, 2014 ; Ball et al, 2017 ). Movement outliers were identified as volumes where movement of the head from one volume to the next was 0.3 mm or greater or had a difference in scaled signal intensity greater than 10, as well as the two volumes before and one after ( Achaibou et al, 2016 ; Goldstein-Piekarski et al, 2018 ; Power et al, 2012 ; Power et al, 2014 ; Siegel et al, 2014 ). The Volterra expansion of twenty-four realignment parameters was also modelled for each task ( Friston et al, 1996 ).…”
Section: Methodsmentioning
confidence: 99%
“…The emotional expression of faces is also obviously an important feature with special representation in the brain [34][35][36][37][38][39][40][41]. We do not argue that any one cue is unimportant or does not have special neuronal representation.…”
Section: Discussionmentioning
confidence: 68%
“…Convincing evidence suggests that the brain is especially well tuned to detect the gaze of others [17][18][19][20][21][22][23]. But the brain is also well tuned to detect facial expression [34][35][36][37][38][39][40][41], and the processing of gaze and facial expression may interact [36,42,43]. In the attention schema hypothesis, the gaze cue should not dominate.…”
Section: Introductionmentioning
confidence: 99%